Arbitragem comercial internacional e acesso à justiça: o novo paradigma do Third Party Funding - Filho, Napoleão Casado (2015)
Arbitration is sometimes seen a Justice system for rich people only. As a private system that needs to be paid, how does it deal with the principle of Acess to Justice? The aim of this thesis is to answer this question and to analyse how Brazilian law should approach the new phenomenon that the world of the International Law is now facing: third parties external to the conflict invest in International Arbitration in exchange for a share of the results of the arbitration proceedings. Throughout the thesis, we demonstrate how the phenomenon of Arbitration emerged in the contemporary world and the great challenges that Arbitration now faces, including the defy of assuring Access to a Jurisdictional Service to parties that do not have enough resources to meet the costs of the arbitration proceedings. We will use the Systems Theory to localize the Arbitration system as an autonomous legal subsystem. Then, we discuss how the world has seen the Third Party Funding phenomenom, concluding with our understanding on how Brazilian law must face this new reality, aligning it with our legal system